1996
DOI: 10.1053/jhep.1996.v24.pm0008903413
|View full text |Cite
|
Sign up to set email alerts
|

New concepts in bilirubin and jaundice: Report of the Third International Bilirubin Workshop, April 6-8, 1995, Trieste, Italy

Abstract: only partial and temporary relief of hyperbilirubinemia; tocytic transporters of UCB and related organic anions extracorporeal liver assist devices have had some sucwere described. Special emphasis was given to the adencess in initial human studies; and inhibition of heme osine triphosphate (ATP)-dependent canalicular multioxygenase (HO) with metalloporphyrins, especially tin specific organic anion transporter that is defective in mesoporphyrin, which markedly decreases bilirubin production for prolonged perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…1 Bilirubin contains two propionic acid groups, and their ionization behavior is implicated in the pigment's hepatic transport, neurotoxicity, formation of gallstones and protein and lipid membrane binding. 2 In a recent investigation of the inter-relationship between altered acidity of synthetic bilirubin analogs and their solution properties, such as stereochemistry, polarity, solubility and excretion, we introduced substituents with a strong electron-withdrawing effect in the vicinity of the carboxylic acid groups. 3,4 Methoxy and methylthio substitution at the a-carbon of each propionic acid of bilirubin was expected to decrease the acid pK a by 1 unit, but this did not significantly change the pigments' overall properties.…”
Section: Introductionmentioning
confidence: 99%
“…1 Bilirubin contains two propionic acid groups, and their ionization behavior is implicated in the pigment's hepatic transport, neurotoxicity, formation of gallstones and protein and lipid membrane binding. 2 In a recent investigation of the inter-relationship between altered acidity of synthetic bilirubin analogs and their solution properties, such as stereochemistry, polarity, solubility and excretion, we introduced substituents with a strong electron-withdrawing effect in the vicinity of the carboxylic acid groups. 3,4 Methoxy and methylthio substitution at the a-carbon of each propionic acid of bilirubin was expected to decrease the acid pK a by 1 unit, but this did not significantly change the pigments' overall properties.…”
Section: Introductionmentioning
confidence: 99%
“…The slope of about 1 between the methods, however, suggests that the difference may be in part systematic. Sample dilution appears to be a major factor (11), and it has been suggested that the effect of sample dilution on the unbound bilirubin might be due to dimerization of albumin (23). This idea is supported by an apparent doubling of the concentration of vacant high-affinity bilirubin binding sites as detected by a sensitive competitive binding technique when plasma is diluted (24).…”
Section: Discussionmentioning
confidence: 99%
“…Metalloporphyrin [11], d-penicillamine [12], phenobarbital and clofibrate [12] are pharmacological agents that can be used in management of hyperbilirubinemia.…”
Section: Introductionmentioning
confidence: 99%